UPAYA KPP PRATAMA MAGELANG UNTUK MENINGKATKAN KEPATUHAN WAJIB PAJAK ORANG PRIBADI DALAM PELAPORAN SPT TAHUNAN PAJAK PENGHASILAN TAHUN PAJAK 2015-2019 - Erwin Budi Setyawan (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2022)
This study discusses how the level of compliance of individual taxpayers in reporting the Annual Income Tax Return at the Pratama Magelang Tax Office where from the results of the research conducted, the results show that the level of participation of individual taxpayers in reporting annual tax returns has fluctuated increases and decreases. In 2015 the level of compliance dropped to 45.60%, still at a low level because of the 79,383 individual taxpayers, only 36,205 taxpayers reported on time. Then in 2016 there was a fairly high increase in compliance compared to previous years and reached a high level, although the number of registered taxpayers who were required to report SPT decreased compared to the previous year. In 2016, the level of compliance reached 79.39%, of which there were 45,637 taxpayers who reported on time out of 57,484 registered taxpayers who are required to submit an SPT. Furthermore, in 2017 there was an increase in the number of registered taxpayers with SPT compared to 2016, which amounted to 70.075 taxpayers. However, in 2017 the level of compliance has decreased to only 58.64% and is at the Medium level because of the 70.075 registered taxpayers who are required to submit an SPT, only 41.090 taxpayers report on time. In 2018 there was an increase in compliance by 1.86% from 2017, which was 60.50%. There are 56,533 registered taxpayers who are required to submit an SPT and who report on time are 34,203 taxpayers and are at the Medium level. Then in 2019 there was an increase again in the number of individual taxpayers who were registered as required to submit an SPT to 60.735, an increase of 4,202. With the number of individual taxpayers who report their SPT on time is 60,231 which results in the percentage being 79.43% with high criteria. Furthermore, if the average compliance level of individual taxpayers in reporting the annual income tax return for the 2015-2019 tax year, the compliance rate is 64.58%. Efforts made by KPP Pratama Magelang to increase the number of mandatory STP reporting for Individual Income Taxes for 2015-2019 are to create programs in order to increase the number of annual SPT reports.), Personal counseling to Taxpayers by AR (Account Representative) at KPP Pratama Magelang, Extension to new Taxpayers by the Extensification Section through Tax Class.